Teaching anticorruption : developing a foundation for business integrity - Stachowicz-Stanusch, Agata. (2013 digital library., 2013)
Over the past few years there has been a surge of interest in discussing how university and business school teaching that focuses particularly on anti-corruption can be developed and become linked to the organizational practices of contemporary businesses. The interest in knowing much more about what exactly constitutes anti-corruption practices and how such practices can become meaningfully integrated in the organizational life of companies that operate in multiple contexts reflects a growing awareness amongst experts, teachers and practitioners of management education of the foundational character of anti-corruption for responsible and sustainable business in today's globalizing world.